INFORMATION ABOUT WH-QUESTIONS AND TAG QUESTIONS (Conferencea, 2022)
wh-questions, a question in English that introduced with a wh-word, that needs information in answer. Question words are used to ask about specific time, quality, place, people and others. Tag questions-is a small question that is attached or tagged to the and of the sentence. These questions constructed by interrogative fragment to add declarative and imperative clauses.